Prevalence and epidemiology of human Cryptosporidium parvum IIc infections in England and Wales. (23rd February 2017) - King, Philippa; Robinson, Guy; Elwin, Kristin; Tyler, Kevin M; Hunter, Paul R; Chalmers, Rachel M
Abstract: Background Cryptosporidium parvum causes acute diarrhoeal disease, long-standing illness in immunosuppressed individuals, and longer-term problems, including stunting in malnourished children. C parvum IIc is a genotype that is genetically distinct, is anthroponotic in contrast to other C parvum genotypes, and is a major genotype causing disease in the developing world. This study aimed to characterise the prevalence and epidemiology of C parvum IIc infections in England and Wales over a 2 year period. Methods: We included C parvum -positive stool samples sent to the Cryptosporidium Reference Unit between Jan 1, 2013, and Dec 31, 2014, by microbiology laboratories in England and Wales. Samples underwent gp60 PCR and sizing of the amplicon to identify presumptive C parvum IIc isolates, which were sequenced for confirmation. Routinely collected epidemiological data were statistically analysed with the χ 2 test. Prior ethics approval had been obtained. Findings: Of the 2641 samples received by the reference laboratory between the study dates, 149 were confirmed to be C parvum IIc, giving a prevalence of 5·6%. C parvum IIcA5G3j was the commonest allele (64%), followed by IIcA5G3a (24%). Male patients were more likely than female patients to be infected with subtype IIcA5G3a (26 [72%] vs 10 [28%], p=0·0179). Most patients were children, with 36 (24%) under the age of 5 years (median age 15 years, IQR 5–33). Sample collection peaked in October of both years. The autumn and winter predominance was particularly strong for the IIcA5G3j allele compared with the IIcA5G3a allele (74 samples of allele IIcA5G3j [80%] and 21 samples of allele IIcA5G3a [62%] collected in autumn and winter, p=0·0407). An unusual IIcA5G2 subtype clustered in the southeast of England. 27 patients with C parvum IIc infection (18%) reported foreign travel, with a significant difference in country visited between alleles IIcA5G3a and IIcA5G3j (15 patients with allele IIcA5G3a travelled outside of Europe vs none with IIcA5G3j, p<0·0001); allele IIcA5G3j was not demonstrated outside of Europe. Interpretation: This study provides the first estimate, to our knowledge, of the prevalence of C parvum IIc in England and Wales, and has shown a clear contrast with less economically developed countries where C parvum IIc is much more common. We have shown IIcA5G3j to be the major allele, which has rarely been reported worldwide, and postulate that it might be a European strain. Limitations of our study include use of routine epidemiological data and low prevalence of samples of certain allele types. Funding: National Institute for Health Research, Norwich Academic Trainees Office, Aquavalens.